Pengembangan Media Boneka Tangan Berkarakter Adat Jawa untuk Meningkatkan Kemampuan Menguraikan Pesan dalam Dongeng - Dewi Safitri; Alfi Laila; Ita Kurnia (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
This study aims to determine the stages, validity and effectiveness of hand puppet media development on the material to describe messages in fairy tales. The research method is R&D with the ADDIE model. The subjects of the study were 10 grade III students of SDN Lirboyo 1 Kediri City who were randomly selected, for the broad trial the subjects were grade III students of SDN Lirboyo 2 Kediri City, totaling 25 students. Model/product validation is carried out through two stages, namely the limited trial phase and the broad trial phase. The data collection instrument is using a questionnaire. The results showed that the stages of developing hand puppet media can be seen from the learning outcomes of students and students' interest in learning Indonesian when using learning media. The validity of media development got a final score of 98% which means it is very valid. The effectiveness of learning media gets a final score of 95% which means it is very effective.